2019
DOI: 10.1002/eat.23198
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between social media use and disordered eating in young adolescents

Abstract: BackgroundThe relationship between social media (SM) use and disordered eating (DE) has not been adequately explored in young adolescents.MethodsData from 996 Grade 7 and 8 adolescents (n = 534 girls; M age = 13.08) was investigated. DE cognitions (Eating Disorder Examination‐Questionnaire [EDE‐Q]), DE behaviors (Project Eating Among Teens), and SM use measures related to Facebook, Instagram, Snapchat, and Tumblr were completed.ResultsDE behaviors were reported by 51.7% of girls and 45.0% of boys, with strict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
91
1
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(123 citation statements)
references
References 33 publications
2
91
1
11
Order By: Relevance
“…eat.23263. https://doi.org/10.1002/eat.23263Wilksch, S.M., O'Shea, A., Ho, P., Byrne, S., Wade, T.D., 2020. The relationship between social media use and disordered eating in young adolescents. Int.…”
mentioning
confidence: 99%
“…eat.23263. https://doi.org/10.1002/eat.23263Wilksch, S.M., O'Shea, A., Ho, P., Byrne, S., Wade, T.D., 2020. The relationship between social media use and disordered eating in young adolescents. Int.…”
mentioning
confidence: 99%
“…Additionally, our findings collected from an online self‐report questionnaire are subject to social desirability bias. Our sample excludes adolescents under 15 who can be affected by EDs and/or engage in ED‐related social networking behavior (Wilksch, O'Shea, Ho, Byrne, & Wade, 2020). We also did not include different response options for transgender male patients versus transgender female patients, limiting the interpretation of our results related to this at‐risk group (Coelho et al, 2019) and representing an important consideration for more accurate gender identity descriptions in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…One difference in the quantitative data suggested that people with AN or OSFED ranked triggering messages on social media as more detrimental than did people with BED. Much has been written around the association between social media use, thin idealisation, disordered eating and eating disorders (45)(46)(47). Thin idealisation online has manifested at the present time in messages around avoiding quarantine weight gain, messages which have been suggested to be dangerous to people with EDs (18,48).…”
Section: Worsening Of Symptoms During the Pandemicmentioning
confidence: 99%